Pengertian, Macam-macam, dan Kegunaan Mempelajari Al-Munasabah - Kaila Cahya Trivina Puteri; Faiq Ahmad Fahleivi Afandi; Dinda Aisyah Huwaina Humaira; Hakmi Hidayat (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Munasabah in the study of Ulumul Qur'an refers to the relationship between Qur'anic verses that are interrelated in a particular context. The main issue discussed is the importance of understanding munasabah in Qur'anic interpretation to reveal a deeper and more comprehensive meaning. The purpose of this study is to explore the concept of munasabah, focusing on the relationship between verses in one surah and between interrelated surahs, and its impact on the understanding of Islamic teachings as a whole. The method used is an analytical approach to classical and contemporary tafsir, by assessing the contributions of mufassirs such as Al-Tabari and Ibn Kathir and the inclusive approach of contemporary mufassirs who consider social and psychological aspects. The results show that understanding munasabah clarifies the interpretation of verses that are often understood separately, thus helping to avoid mistakes in understanding divine revelation. Thus, the understanding of munasabah is crucial to produce appropriate and relevant interpretations in the context of Muslim life, as well as strengthening the relationship between the teachings of the Qur'an and the social realities faced by society.